Menimbang Kompatibelitas Multikulturalisme dan Islam: Ikhtiar Menggagas Pendidikan Islam Multikultural di Indonesia - Mukhlis Mukhlis (Universitas Islam Negeri Mataram, 2008)
The concept of multiculturalism has expanded across countries borders and become an important topic in various discourses on cultural diversity. Moreover, many authors have related the concept to other concepts such as education so that many books and articles on multicultural education have been written recently. This article is not merely aimed at relating multiculturalism to Islamic education, but also giving critical analysis to its historical background and philosophical bases. To go further, I examine the opportunity to adopt multiculturalism in the point of view of Islamic doctrines and to implement it in Islamic education in Indonesia. In conclusion, multiculturalism is not only valid theologically and doctrinally, but also it is a must socially, culturally, and politically imperative. Therefore, the implementation of multiculturalism in various aspects of Islamic education must be performed smartly and carefully from the phase of input, process, and output to outcome